Approach to the assessment of sediment quality in Florida coastal waters - MacDonald Environmental Sciences, Ltd.; Florida. (MacDonald Environmental Sciences, Ltd., 1994)
Tracings: SQAG (sediment quality assessment guidelines).
"November 1994."
Bibliography: p. 107-121 (v. 1); p. 49-52 (v. 2).
v. 1. Development and evaluation of sediment quality assessment guidelines -- v. 2. -- Application of the sediment quality assessment guidelinesFUFTaSUFBoU
Tracings: SQAG (sediment quality assessment guidelines).
The purpose of this report is to recommend a scientifically defensible framework for assessing the biological significance of sediment-associated contaminants. Numerical SQAGs are integral to this framework, providing the basis for assessing potential effects of sediment-associated contaminants. A variety of approaches for deriving sediment quality assessment values were reviewed to identify those that would be applicable to Florida coastal conditions. The results of this review indicate that each approach has deficiencies which limit its direct applicaiton in Florida. For this reason, an integrated strategy for deriving numerical SQAGs is recommended for the state of Florida. The recommended strategey is designed to provide relevant assessment tools in the near-term and allows for refining these guidelines as additional data become available. Using the recommended approach, numerical SQAGs were developed for assessing sediment quality in Florida coastal waters. The metals interpretive tool and the preliminary SQAGs were used to conduct an initial assessment to detrmine the nature, extent, and severity of contamination in Florida coastal sediments.
Keywords: Marine sediments / Florida.; Coastal zone management / Florida.; Sedimentation and deposition / Research / Florida.